The demon of politics.
1 online resource (304 pages).
Keywords: Mario Tronti is considered one of the most important Italian Marxist philosophers of our time, as well as one of the most influential European political theorists of the post-war period. Largely untranslated and hence unknown in the anglophone world, this is the first volume of a two-volume translation, The Demon of Politics, presenting an invaluable picture of Tronti's political life and intellectual activity through a selection of his most relevant writings.Volume I paints a fascinating picture of Tronti's work in the 1960s, when he made landmark contributions to a new reading of Marx, and in the 1970s when he again joined the Communist Party and worked towards a theory of the political that led to lively debates and even splits within workerism. An introduction written by the editors contextualises the writings of the first part of Tronti's career, while also providing the biographical and political details necessary to understand the evolution of his thought during the 1950s, 1960s, and 1970s. Footnotes throughout the volume provide valuable precisions and elements of contextualisation.The volumes of The Demon of Politics offer the most comprehensive edition of Tronti's works available to students and scholars.